Alcohol use, harmful use of alcohol and probable dependence among residents of a selected fishermen community in South India: A community based cross-sectional analytical study - Vaithiyanathan, Purushothaman; Thekkur, Pruthu; C., Kamashvell; Datta, Shib Sekhar (International Journal Of Community Medicine And Public Health, 2018)
Background: Alcohol use is prevalent among fisherman community. In this regard, a community based survey was conducted among adults in the fisherman community of Puducherry a) to determine prevalence of alcohol use, harmful use and probable dependence b) to assess the factors associated with alcohol use and harmful use of alcohol. Methods: A community based cross-sectional analytical study was conducted in a selected coastal commune Panchayat of Puducherry, South India during April, 2016 to March, 2017. The named streets were selected as the clusters. In each of the selected street first seven houses on the right hand side were enrolled. A semi structured questionnaire was used to collect details regarding socio-demographic variables and WHO AUDIT tool was used to detect the harmful use and probable dependence. Data was entered in Microsoft Excel and analyzed using Stata 12 software. The association between the individual’s characteristics and alcohol use, harmful use of alcohol were assessed using generalized linear models with poisson distribution and log link function. Results: The prevalence of alcohol use was 152 (61.5%, 95% CI- 55.4%-67.5%), 63 (25.5%, 95% CI- 20.4%-31.2%) had harmful use of alcohol and 20 (8.1%, 95% CI- 5.2%-12.0%) had probable dependence to alcohol. The multivariate regression showed that age between 31 to 59 years and tobacco use (1.7 (95% CI- 1.4-2.0)) were independently associated with alcohol use. The multivariate regression showed that being illiterate (2.1 (95% CI- 1.2-3.6)), being graduate (3.2 (95% CI- 1.5-6.6)), currently married (2.2 (95% CI-1.1-5.0)), tobacco use (1.4 (95% CI- 1.1-1.9)) and family history (1.4 (95% CI- 1.1-1.9)) were independently associated with alcohol use. Conclusions: The present study showed very high prevalence of alcohol use and harmful use of alcohol in coastal villages. Stringent regulatory approaches and effective health education approaches were much needed for the control of alcohol use and harmful use of alcohol.